Radiofrequency Rejuvenation of the “Tweener” Patient: Under, Over, or Through the Skin - Kam, Joanna; Frost, Ariel; Bloom, Jason D. (Facial Plastic Surgery, 2021)
The demand for noninvasive facial rejuvenation continues to increase as younger, well-informed patients enter the aesthetic market. We refer to a subset of these patients as “tweeners,” those who present with early signs of neck and facial aging, but who have not yet developed changes significant enough to warrant a traditional excisional surgery approach. Many of these patients are in search of a minimally invasive intervention, a bridge in between observation and surgery. The authors describe their experience with radiofrequency (RF) technology as an in-office tool to address the aging face in a select patient population. This review also attempts to comprehensively search the existing body of literature to describe the RF technologies and devices available for facial rejuvenation. The efficacy and safety profiles of the devices are discussed, and the devices are categorized by their method of RF delivery—over (contact), through (microneedle), and under (percutaneous) the skin.
Keywords: radiofrequency; percutaneous; microneedling; minimally invasive facial rejuvenation